2020
DOI: 10.1016/j.concog.2020.103031
|View full text |Cite
|
Sign up to set email alerts
|

Selfhood triumvirate: From phenomenology to brain activity and back again

Abstract: Recently, a three-dimensional construct model for complex experiential Selfhood has been proposed (Fingelkurts et al., 2016b,c). According to this model, three specific subnets (or modules) of the brain selfreferential network (SRN) are responsible for the manifestation of three aspects/features of the subjective sense of Selfhood. Follow up multiple studies established a tight relation between alterations in the functional integrity of the triad of SRN modules and related to them three aspects/features of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(92 citation statements)
references
References 263 publications
(486 reference statements)
3
89
0
Order By: Relevance
“…Considering the V-SRP studies together, a pattern of functional segregation seems to emerge between the left IPL and the MPFC. Results suggest that the left IPL may be involved in determining the self-relevance of verbal information as primarily tested by the neutral V-SRP studies of SPE (Figure 3), while the MPFC might be more so involved in the affective evaluation of such information as tested primarily by the emotional SRP studies of SEB (Figure 4), consistent with several functional network models of SRP (Fingelkurts et al, 2016(Fingelkurts et al, , 2020Frewen et al, 2020). Further, considering the midline posterior cortex, Lou et al (2004) and Kwan et al (2007) applied TMS over Pz and found smaller degrees of impact on V-SRP compared to the MPFC, while De Pisapia et al (2019) found that MPFC had an impact on both the PCC and the bilateral IPL BOLD signals during emotional V-SRP.…”
Section: Verbal Srp (V-srp)supporting
confidence: 71%
See 2 more Smart Citations
“…Considering the V-SRP studies together, a pattern of functional segregation seems to emerge between the left IPL and the MPFC. Results suggest that the left IPL may be involved in determining the self-relevance of verbal information as primarily tested by the neutral V-SRP studies of SPE (Figure 3), while the MPFC might be more so involved in the affective evaluation of such information as tested primarily by the emotional SRP studies of SEB (Figure 4), consistent with several functional network models of SRP (Fingelkurts et al, 2016(Fingelkurts et al, , 2020Frewen et al, 2020). Further, considering the midline posterior cortex, Lou et al (2004) and Kwan et al (2007) applied TMS over Pz and found smaller degrees of impact on V-SRP compared to the MPFC, while De Pisapia et al (2019) found that MPFC had an impact on both the PCC and the bilateral IPL BOLD signals during emotional V-SRP.…”
Section: Verbal Srp (V-srp)supporting
confidence: 71%
“…However, neuroimaging findings in response to SRP tasks further differentiate response among these ROIs. For example, V-SRP is known to be at least partially mediated by DMN activity in the medial prefrontal cortex (MPFC), posterior cingulate cortex (PCC), ventral precuneus, and the bilateral IPL (e.g., Araujo et al, 2015;Davey et al, 2016), although the response to different kinds of meditation practices suggest that it may be particularly the left more so than the right IPL that is associated with V-SRP (e.g., Fingelkurts et al, 2016;Fingelkurts et al, 2020). In contrast, NV-SRP emanating from the inner body (i.e., interoception; e.g., heartbeat) or the outer body (i.e., exteroception; e.g., touch) is assessed during tasks that engage attention toward bodily self-consciousness (BSC) (reviewed by Park and Blanke, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Margulies et al 2009;Zhang and Li, 2012). Further functional specialization may exist between left and right precuneus (Cavana and Trimble, 2006;Fingelkurts et al 2020).…”
Section: The Central Precuneus Network For Nondual Awarenessmentioning
confidence: 99%
“…Since those observations, many further functions were shown to be associated to this network. Other than self-referential and emotional processes (Buckner and Carroll, 2007; D’Argembeau et al, 2010; Denny et al, 2012; Engen et al, 2017; Fingelkurts et al, 2020; Fossati et al, 2003; Knyazev et al, 2020; Molnar-Szakacs and Uddin, 2013; Northoff et al, 2006; Northoff and Bermpohl, 2004; Ochsner et al, 2005, 2004; Satpute and Lindquist, 2019; Uddin et al, 2007), the DMN turned out to be related to memory and mental time-travel (Addis et al, 2007; Cabeza et al, 1997; Foster et al, 2012; Kim, 2016; Murphy et al, 2018; Rugg and Vilberg, 2013; Schacter et al, 2008, 2007; Spreng et al, 2015; Svoboda et al, 2006; Yang et al, 2013), mental simulation and scene construction (Gerlach et al, 2011; Hassabis et al, 2007; Hassabis and Maguire, 2007; Spreng and Grady, 2010), theory of mind (ToM) and social cognition (Amft et al, 2015; Mar, 2011; Mars et al, 2012; Mwilambwe-Tshilobo and Spreng, 2021; Rilling et al, 2004; Ruby and Decety, 2004; Saxe and Kanwisher, 2003; Saxe and Powell, 2006; Spreng and Andrews-Hanna, 2015), moral judgment (Bzdok et al, 2012; Greene et al, 2001; Harrison et al, 2008; Pujol et al, 2008), semantic processing (Binder et al, 1999, 2009; Chiou et al, 2020; Evans et al, 2020; Lanzoni et al, 2020), and reward mechanisms (Lopez-Persem et al, 2020; Martins et al, 2021; Xue et al, 2009). However, most of these psychological functions can still be somewhat associated with the resting state (Wen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%